An investigation of the key mechanisms that promote whole school development in a secondary school pilot project context - Westraad, Susan Fiona (Rhodes University, Faculty of Education, Department of Education, 2007)
Providing relevant and quality schooling for all South African learners is the paramount goal of the South African National Department of Education. South Africa 's historical and current socio-economic contexts provide many challenges for both the Department of Education and schools in this endeavour to provide quality teaching and learning. These challenges impact directly and indirectly on what happens in the classroom. Since 1994 a plethora of education and training policy has been introduced in South Africa to redress historical imbalances; to introduce a new education and training framework and approach; and to provide guidelines, principles and procedures for addressing some of the challenges that impact on schools. The National Whole School Evaluation Policy provides the legislative framework for the establishment of a quality assurance process in South African schools based on accountability and support. The subsequent Integrated Quality Management System attempts to provide a framework for integrating school evaluation and performance measurement. Policy frameworks are in place to guide quality assurance and school improvement, however, the reality of implementing this at a grass roots level is particularly challenging. The General Motors (GM) South Africa Foundation, a non-governmental development organisation, established by General Motors (GM) South Africa, commenced with the piloting the Learning Schools Initiative to investigate some of the challenges of whole school development and evaluation. This research documents the Learning Schools Initiative's intervention with the initial two pilot secondary schools situated in Port Elizabeth (Nelson Mandela Bay) over a four-year period. It reviews the relevant school reform and school development literature and adopts a critical realist evaluative research approach to investigate the key mechanisms that promote whole school development and change in this context. In keeping with this approach, the results of the research are analysed and discussed within a context-menchanism-outcome configuration that involves the identification of the key mechanisms that bring about desired outcome/s in a specific context. Seven key generative mechanisms are identified as critical at a school and classroom level (i) school culture, (ii) school structures, (iii) effective leadership and management, (iv) personal growth and meaning, (v) restoration of relationships, (vi) professional development of educators, and development of capacity to work together, and (vii) support and accountability. The need to structure school development interventions around the triggering of identified key mechanisms is also identified as an important overarching mechanism. Suggestions are made for further research required to facilitate a deeper understanding of how to bring about meaningful change that results in quality teaching and learning in South African schools.
Keywords: Education -- South Africa; Education, Secondary -- South Africa; Education and state -- South Africa; School improvement programs -- South Africa; Educational change -- South Africa